2015
DOI: 10.1002/wsbm.1319
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated genome engineering through multiplexing

Abstract: Throughout the biological sciences, the past fifteen years have seen a push towards the analysis and engineering of biological systems at the organism level. Given the complexity of even the simplest organisms, though, to elicit a phenotype of interest often requires genotypic manipulation of several loci. By traditional means, sequential editing of genomic targets requires a significant investment of time and labor, as the desired editing event typically occurs at a very low frequency against an overwhelming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…A significant advantage of using dCas9 as DNA binding domain is the great ease of multiplexing. 21 By simply coexpressing multiple gRNAs targeting multiple genes, dCas9 activators can be recruited to multiple loci across the genome and activate expression of multiple genes simultaneously. This is particularly important in applications where multiple genes have to be activated to carry out a certain biological process.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A significant advantage of using dCas9 as DNA binding domain is the great ease of multiplexing. 21 By simply coexpressing multiple gRNAs targeting multiple genes, dCas9 activators can be recruited to multiple loci across the genome and activate expression of multiple genes simultaneously. This is particularly important in applications where multiple genes have to be activated to carry out a certain biological process.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A more recent study reported improved heavy metal biosorption capacities for E. coli cells engineered with mice MT1, demonstrating the potential of the genetic engineering approach in developing organisms with tailored and improved biosorption capacities ( Almaguer-Cantú et al, 2011 ). The introduction of modern research technologies in genomics such as next generation sequencing ( El-Metwally et al, 2014 ) and high throughput genome editing techniques ( Bao et al, 2016 ) allowed the study of organisms with potential biosorption capacities that are expected to have several bioremediation applications in future.…”
Section: Potential Strategies For Bioremediationmentioning
confidence: 99%
“…The clustered regularly interspaced short palindromic repeats (CRISPR) system has been recently developed for multiplex genome engineering in nearly all kingdoms of life 7 10 . In this modular and highly efficient system, a guide RNA (gRNA) recruits a CRISPR nuclease to a specific region of the genome to create in a double strand break.…”
Section: Introductionmentioning
confidence: 99%